Remittances and the brain drain - Riccardo Faini (Institute for the Study of Labor (IZA), 2006)
In most destination countries, immigration policies are increasingly tilted toward the most skilled individuals. Whether this shift hurts economic prospects in sending countries, as argued by the traditional brain drain literature, is somewhat controversial. The most recent literature has focused on the link between skilled out-migration and educational achievements. In this paper, we emphasize a different channel. It is often argued that skilled migrants raise economic welfare at home thanks to a relatively larger flow of remittances. Skilled migrants typically earn relatively more and, ceteris paribus, will therefore remit more. However, they are also likely to spend a longer span of time abroad and also are more likely to reunite with their close family in the host country. Both factors should be associated with a relatively smaller flow of remittances from skilled migrants. Hence, the sign of the impact of the brain drain on total remittances is an empirical question. We first develop a simple model showing that skilled migrants may have indeed a lower propensity to remit home out of a given flow of earnings abroad. We then derive an empirical equation of remittances and estimate it on a large panel of developing countries. As a measure of the brain drain, we use the dataset by Docquier and Marfouk (2004) that in turn builds on the pioneering work of Carrington and Detragiache (2004). We find considerable evidence that the brain drain is associated with a smaller flow of remittances.
Keywords: F02; F22; 330; remittances; migration; brain drain; Rücküberweisung (Migranten); Brain Drain; Welt